Power of kongsi Merdeka - Abd Razak, Dzulkifli (2005)
AS we celebrate Merdeka on Aug 31, it may be useful to revisit a concept that was deemed to be the lynchpin towards an independent Malaya and subsequently Malaysia in less than two decades later. This is the concept of perkongsian, an unwritten social contract of sort between the various communities. Vaguely, perkongsian can be translated to mean "sharing", but not quite. The root word, kongsi, is of Chinese origin and has at least two meanings. Summarily, one refers to a shared place of community living which could be likened to a presentday idea of a dormitory, except that a kongsi then was used to house Chinese coolies.